História de vida, demografia e conservação de quelônios: da perspectiva local à global - Lucas, Priscila da Silva (2016)
Biodiversity faces increasing pressure derived from human action, including habitat alteration and degradation, fragmentation, climate change, exploitation of species and pollution. Consequently, assessments of various species show extremely high extinction rates. Roads and other linear infrastructures are one of the greatest landscape modifiers nowadays, especially in tropical regions. These linear clearings cause numerous impacts that are better understood, but not exclusive, on a local scale. In a broader scale, an increase in road density leads to an increased loss of natural habitats and then, there is a distinguished decrease on the remaining patch size that affects population persistence. A good knowledge of the species life history is the first step and essential for the development of conservation strategies, to keep the long-term persistence and recover declining populations. Thus, this thesis throughout the following chapters seeks to quantify basic life history parameters, especially those related to reproduction in different populations, the relationship between reproductive parameters and between them and maternal body size. In addition, we aimed to use this life history information with demographic parameters to estimate population growth rates for Trachemys dorbigni in a region with many sources of threat to the species persistence. Finally, we used life history parameters, population dynamics, road mortality data and land use (road network) information and species distribution data in a spatially explicit model that quantifies critical values of maximum density and minimal patch size that allow the persistence of populations of turtle species in landscapes fragmented by roads. In general, reproductive strategies (mainly egg size) of D’Orbigni slider vary between populations and with body size. Species populations near the highway BR-471 at ESEC Taim may be declining due to the threats observed in the area (turtle road-kill and removal of eggs for pet trade). Adult females is the main stage where we should focus efforts for conservation programs of the species in locations within the distribution and that suffers with the same potential impacts. In the global assessment, we observed many regions, especially in North America and Asia, many species already have smaller patch size than the viable size to their persistence. These regions are those with the highest density of highways. We hope that the results of this study may direct future studies, be used by government agencies for implementation of specific mitigation measures, conservation actions and planning the improvement or construction of new roads.